Предмет: Математика,
автор: gurzuf2001
12+3(2(х-1)4) = 6(х+1)
Ответы
Автор ответа:
0
12+3(2x-2)4)=6x+6
12+(6x-6)4)=6x+6
12+(24x-24)=6x+6
12+24x-24=6x+6
-12-6=6x-24x
-18=-18x
x=-18:(-18)
x=1
12+(6x-6)4)=6x+6
12+(24x-24)=6x+6
12+24x-24=6x+6
-12-6=6x-24x
-18=-18x
x=-18:(-18)
x=1
Автор ответа:
0
и уже сама решила! благодарю за помощь!!!
Автор ответа:
0
????
Автор ответа:
0
окей
Автор ответа:
0
ага
Похожие вопросы
Предмет: Кыргыз тили,
автор: rnematovna222
Предмет: Математика,
автор: Artem20785
Предмет: Литература,
автор: Аноним
Предмет: Химия,
автор: Aigiza14